Donation of Constantine and Constitutum Constantini The Misinterpretation of a Fiction and its Original Meaning. With a contribution by Wolfram Brandes: The Satraps of Constantine - Fried, Johannes (Millennium-Studien / Millennium Studies, 2012)
The Donation of Constantine is the largest and most powerful forgery in world history. Disputed until modern times, this document was the fuel of religious war, used by both the reformation, as well as the counter-reformation. Johannes Fried not only reinterprets the origin of this forgery (i.e. he ascribes it to the Franks` opposition of Emperor Louis the Pious), but retells, as well, the history of its misinterpretation since the High Middle Ages.